Short-Term Energy Load Forecasting Model with Sample Filtering - Kateule, Ruthbetha; Sakala , Lucas A.; Tunga, Mahadia (Tanzania Journal of Science, 2023)
Short-term energy load forecasting is a crucial task in the power smart grid, which enables the power utilities to understand the future energy demands and plans to attain the demand and supply equilibrium, thereby optimizing power deployment and reducing power losses. Several techniques have been implemented to enhance energy load forecasting. However, the nonlinear nature of the data collected in the smart grid makes it difficult to attain 100% energy load forecasting accuracy. For instance, the Deep Feedforward Neural Networks model based on Input Attention Mechanism and Hidden Connection Mechanism has a mean absolute percentage error of 3.17%; model based on Sequence to Sequence Recurrent Neural Network with Attention had a mean absolute percentage error of 2.7%. The model based on Deep Recurrent Neural Networks with Levenberg–Marquardt backpropagation algorithm had a mean absolute percentage error of 0.58; and Deep Feedforward Neural Network with sample weights model had 3.22 % as root mean squared error. To improve energy load forecasting accuracy, this work proposed a model based on Deep Recurrent Neural Networks and sample filtering, which provides an exhaustive elucidation for modelling a sophisticated stochastic relationship between the input and output features. Deep Recurrent Neural Networks have proven to be good at modelling the nonlinearities in data of different fields and are mostly used in energy load forecasting to reduce forecasting error and a high degree of overfitting. Sample filtering is achieved through the use of K-Means clustering which determines the number of clusters to be used in the model. Findings from the study showed that by employing Deep Recurrent Neural Networks and sample filtering, the short-term energy load forecasting accuracy is improved in reference to mean absolute percentage error and root mean squared error of 0.31% and 1.014, respectively. As a result of the reduction in error, the energy demand and supply chain equilibrium are enhanced, thereby optimizing power deployment and reducing power losses. Keywords: Machine learning, Neural networks, Sample filtering, Smart grid, Short-term energy forecasting